Misapplication of Acetic Acid During The Colposcopy: A Case Report - Dede, Murat; Alanbay, İbrahim; Ulubay, Mustafa; Karaşahin, Emre; Gezginç, Kazım; Yenen, Müfit Cemal (Gynecology Obstetrics & Reproductive Medicine, 2008)
A vaginal mucosa chemical burn injury because of the misapplication of 98% acetic acid in colposcopic examination, which was treated with local oestrogen and antibiotics safely and efficiently is presented. A 28 years old G0 P0 patient had menorrhagia and Atypic Squamous Cell-High Grade (ASC-H) in her pap smear. During the pelvic examination, myoma uteri was diagnosed, and myomectomy with a colposcopic examination under general anestesia was planned. In the operation room, instead of 5% acetic acid, 98% acetic acid solution for colposcopic examination was misapplied under general anestesia. In a few minutes vaginal mucosa was erythematous and bullous because of corrosive vaginal burn injury. Vaginal mucosa was immediately irrigated with saline infusion and treated with local oestrogen and antibiotics. After two weeks, chronic erosive cervisitis was seen on the cervix and no visible sign of erythematous and bullous structure was apperent in the vagina. Full recovery took two weeks. Topical vaginal oestrogen is a safe, convenient and easy to apply treatment option for vaginal chemical burn injuries.